Pansies : how to grow, reimagine, and create beauty with pansies and violas - Estrada, Brenna (Timber Press, 2025)
"Pansies is the big idea flower book we've all been waiting for. While working at the famed Floret Flower Farm, Brenna Estrada was so inspired by the pansies being grown that she began to trial hundreds of varieties of pansies and violas on her own farm. Her innovative approach to growing in full sun results in pansies with long stems, breathtaking fragrance, and unique color. Filled with stunning photography, Pansies is perfect for growers, florists, artists, and collectors."--